توظيف اللقطة القريبة في الإعلان التلفزيوني. - اسماء عباس لفته (Journal of Babylon Center for Humanities Studies, 2025)
Cinema has been an important element since its emergence to this day, especially since it recorded many of the moments of our lives, which greatly influenced it. This influence spread to many other arts, and advertisements were one of the things that benefited from this technology, whose makers excelled at inventing a wide range of forms that could Affect nature Our feelings and feelings, so the films varied according to the diversity of the doctrines they produced. This is on the one hand, and on the other hand, technically, the forms of these shots and the ways of designing their movement varied. Therefore, the researcher formulated the title of her research entitled (Using the close-up shot in television advertising), which consisted of three chapters. The first chapter included the methodological framework that included the problem. search The limits of the research and a set of definitions for all the terms mentioned in the title, while the second chapter included the theoretical framework that consisted of two sections, the first under the title (the close-up shot and its effect on the recipient), while the second section came under the title (the effect of the operation of the shot size in television advertising) with a set of indicators that were produced. About this chapter As for the third chapter, it included the research procedures and samples that the researcher chose to analyze according to those indicators, leading to the results and conclusions that she reached. The fourth chapter also included the group of sources that the researcher used in writing her research.